Diversity and cellulolytic potential of gut bacteria isolated from Blaberus and Panesthia cockroaches in Aceh, Indonesia - SABARIAH SABARIAH; SUHARTONO SUHARTONO; ALIA RIZKI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sabariah S, Suhartono S, Rizki A. 2025. Diversity and cellulolytic potential of gut bacteria isolated from Blaberus and Panesthia cockroaches in Aceh, Indonesia. Biodiversitas 26: 5145-5155. Forest-dwelling cockroaches harbor diverse gut microbiota capable of degrading complex organic compounds, particularly cellulose. This study investigated the diversity and cellulolytic potential of gut bacteria isolated from two cockroach genera, namely Blaberus and Panesthia, collected from the Soraya Research Station, Aceh, Indonesia. Ten individuals of each species were collected between January and March 2025 using standardized pitfall traps and hand collection methods. Through systematic isolation and characterization, a total of 19 bacterial isolates were isolated comprising 10 from Blaberus and 9 from Panesthia. Morphological and biochemical analysis revealed diverse bacterial genera, with Blaberus harboring Klebsiella, Bacillus, Flavobacterium, Pseudomonas, Salmonella, and Staphylococcus, while Panesthia contained predominantly Bacillus (55.5%) along with Salmonella, Staphylococcus, and Enterococcus. Three isolates from Blaberus demonstrated cellulose-degrading capabilities, Bacillus, Flavobacterium, and Pseudomonas with cellulolytic indices of 0.08, 2.45, and 3.08, respectively. Gas Chromatography-Mass Spectrometry analysis revealed high concentrations of linoleic acid in these cellulolytic isolates. These findings are the first study of cellulolytic bacteria from forest cockroaches in Indonesia's unique Aceh ecosystem, enhancing understanding of tropical forest nutrient cycling and demonstrating significant potential for sustainable biotechnological applications in enzyme production and bioconversion processes.